Regional Differences in Chinese Female Demand for Childcare Services of 0-3 Years: The Moderating and Mediating Effects of Family Childcare Context - Chuanfang Chen; Huimin Hu; Renbing Shi (MDPI AG, 2023)
There are multiple reasons to consider the use of formal childcare: parental employment, child development, fertility choices, elderly health, generational relations, etc. This study explores the relationship between regional differences (urban/rural; eastern/central/western) and demand for childcare services (quantity, price, quality) from birth to three years of age, moderated and mediated by the family childcare contexts among Chinese women. Altogether, 1770 mothers of children aged 0-3 were selected from a national survey and analyzed. There are three major findings: (1) Urban mothers show a willingness to spend on the higher monetary cost of center-based childcare compared to rural mothers, as a result of more severe work-child conflicts faced by urban women. Urban-rural gaps in individual and household income also contribute to the differences in affordability. (2) Mothers in eastern China have a more substantial need to place their infants or toddlers in nurseries before the age of three than their counterparts in central and western China, primarily due to a lack of grandparental and paternal childcare support and an expectation of higher quality programs. (3) There is no significant regional disparity in terms of care-related or education-related quality preferences. The paper proposes regional prioritized strategies and targeted services to address the "3A" problems of childcare provision.